2019
DOI: 10.1002/tqem.21647
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the factors affecting environmental risks of projects using a hybrid approach of DEMATEL‐ANP, artificial neural network: A case study

Abstract: The increasing growth of the economy in each country necessitates a great amount of investment in infrastructure. The belief that projects involve various uncertainties, such as technical skills, management quality, and the like, indicates that most projects fail to achieve their aims, interests, costs, as well as their timeframes and space requirements. As the environment can pose significant uncertainty to any project, environmental risks should be deeply studied by project management departments. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…At present, decision‐making is more complex due to the interactions between internal and external variables, the involvement of several actors in the process, resource and supply issues, market implications, environmental factors, the rapid pace of technological changes, and the impacts caused by production growth and diversification. Hence, the relevance of developing studies focused on sustainability and using multicriteria models, since these are crucial tools to address complex, subjective decisions with high degrees of uncertainty (Ershadi & Ashtiyani, 2019; Wang, 2010).…”
Section: Sustainability Decision Support Theorymentioning
confidence: 99%
“…At present, decision‐making is more complex due to the interactions between internal and external variables, the involvement of several actors in the process, resource and supply issues, market implications, environmental factors, the rapid pace of technological changes, and the impacts caused by production growth and diversification. Hence, the relevance of developing studies focused on sustainability and using multicriteria models, since these are crucial tools to address complex, subjective decisions with high degrees of uncertainty (Ershadi & Ashtiyani, 2019; Wang, 2010).…”
Section: Sustainability Decision Support Theorymentioning
confidence: 99%
“…The research findings indicated that specifying three areas and presenting the necessary solutions to improve HSE management under optimal conditions caused the exploitation of pipelines (Dana et al , 2018). Ershadi and Ashtiyani (2019) presented an artificial neural network model for appraisal of importance weights for environmental risks. Bandarja (2014) evaluated the HSE risk assessment of the hydrocracker unit in the Oil Refining Company of Bander Abbas.…”
Section: Review Of Literaturementioning
confidence: 99%